'We secured the tussac': Accounts of ecological discovery, exploitation and renewal in the Falkland Islands. Issue 4 (6th October 2019) - Tourangeau, Wesley; Sherren, Kate; Delignières, Marilou
Abstract: Sheep farms dominate the Falkland Islands landscape and have for over a century. The introduction of sheep, and several other species, has significantly transformed the ecology of this archipelago—the near elimination of tussac grass being one of the most notable changes. Tracing back to early accounts of tussac grass in the 'Falklands', this paper captures its discovery, exploitation and current stage of renewal, including a closer look at the connections between tussac and livestock farming, as well as parallel trends in other countries. We narrate changing relations between people and tussac grass using a combination of interview data, historical accounts and scientific literature. Tussac is presented as a historical bellwether of shifting trends in local farm and environmental management in this isolated archipelago. Shifts in land ownership, grazing management methods and conservation efforts are bringing momentum to a period of renewal across the Falklands. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.